PENDIDIKAN TRANSFORMATIF DALAM UPAYA MENGATASI MASALAH PUTUS SEKOLAH DI WILAYAH DAERAH TERTINGGAL: STUDI KASUS KABUPATEN JEMBER PROVINSI JAWA TIMUR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the issue of school dropout in underdeveloped areas and examine the implementation of transformative education as a strategy to reduce dropout rates in Jember Regency, East Java. The research employs a qualitative approach with a case study method conducted in several districts with low educational participation rates. The research subjects include teachers, students, principals, parents, and local education authorities. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using the Miles and Huberman model. The findings reveal that the main factors contributing to school dropout include family economic conditions, low learning motivation, limited access to education, and the lack of curriculum relevance to local contexts. The implementation of transformative education through contextual learning, dialogical teaching methods, and community involvement has proven to enhance students’ motivation, critical awareness, and participation in education. Therefore, transformative education can serve as an effective approach to addressing dropout issues in underdeveloped areas by empowering individuals and communities in a sustainable manner.